If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 18 = -2(x + 6) Combine like terms: -16 + 18 = 2 2 = -2(x + 6) Reorder the terms: 2 = -2(6 + x) 2 = (6 * -2 + x * -2) 2 = (-12 + -2x) Solving 2 = -12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + 2x = -12 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + 2x = -12 + 0 2 + 2x = -12 Add '-2' to each side of the equation. 2 + -2 + 2x = -12 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -12 + -2 2x = -12 + -2 Combine like terms: -12 + -2 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| -4=-1-3 | | .5(4x+14)=2(2x-7) | | 125c^2-180= | | .4y+6=31 | | 0.5x-0.75y=-2 | | 9=6(x+6)-7x | | h=160t-16t^2 | | -22-7x=48 | | 4(x-1)-4=2x+2(-3+x) | | u/4=-8 | | 9-0.7k=9 | | 2.37=.87h-.25 | | -5(6+5p)=136 | | -9x-36=90 | | 1+x+7-9x=-24 | | 16x-2=40x+16 | | 22=13+x | | 8a+3(-7)=3 | | -2b/13=8/3 | | a^12=5 | | 54+8x=158 | | (3x+8)=5x | | 6x-9=21+6x | | 18-3y=12 | | 2x-5=2(x-7) | | 30+3x=78 | | 6k^2-42+72=0 | | 1-121x^2= | | .4545454545h+.77777777=.22222222 | | 0.833y-0.142=0.50 | | -6m+8m=-5+2m-1 | | 6-2x-2x=26 |